2000
DOI: 10.1149/1.1394109
|View full text |Cite
|
Sign up to set email alerts
|

Remarkably Active Catalysts for the Electroreduction of O[sub 2] to H[sub 2]O for Use in an Acidic Electrolyte Containing Concentrated Methanol

Abstract: Focusing on methanol tolerance, a series of heat-treated metalloporphyrins were investigated by steady-state voltammetry with a rotating disk electrode. The heat-treated CoTPP/FeTPP (tetraphenylporphyrin) shows the optimum catalytic activity for oxygen reduction with an onset catalytic potential [0.9 V vs. reversible hydrogen electrode (RHE)] close to that of platinum black catalyst (1.0 V vs. RHE). However, the catalytic activity for oxygen reduction on platinum black catalyst is severely affected by the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
91
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(94 citation statements)
references
References 22 publications
3
91
0
Order By: Relevance
“…Another approach is to develop methanol-tolerant cathode catalysts such as binary platinum alloys containing Co, Ni, Fe and Cr [5][6][7]. Various transition-metal macrocycles [8][9][10] and ruthenium-based chalcogenides [11,12] have also been tested as methanol-tolerant oxygen cathodes because these compounds are inactive toward the oxidation of methanol. However, the catalytic activities of these catalysts for the oxygen-reduction reaction (ORR) are still lower than those of Pt-based catalysts, and the long-term stability under fuel cell conditions at high potentials has not been well tested as compared to Pt-based catalysts [13].…”
Section: Introductionmentioning
confidence: 99%
“…Another approach is to develop methanol-tolerant cathode catalysts such as binary platinum alloys containing Co, Ni, Fe and Cr [5][6][7]. Various transition-metal macrocycles [8][9][10] and ruthenium-based chalcogenides [11,12] have also been tested as methanol-tolerant oxygen cathodes because these compounds are inactive toward the oxidation of methanol. However, the catalytic activities of these catalysts for the oxygen-reduction reaction (ORR) are still lower than those of Pt-based catalysts, and the long-term stability under fuel cell conditions at high potentials has not been well tested as compared to Pt-based catalysts [13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Jiang and Chu [14,15] synthesized a series of single and binary heat-treated metalloporphyrins (such as HT-CoTPP, HT-FeTPP, and HT-FeTPP/CoTPP) and evaluated their catalytic activity for the ORR. They found that the catalytic activity of binary FeTPP/CoTPP catalysts was much better than that of single CoTPP or FeTPP.…”
Section: Introductionmentioning
confidence: 99%
“…Non-noble metal catalysts based on chalcogenides [36][37][38][39] and macrocycles of transition metals [40][41][42][43][44] have shown good activity for the ORR. However these materials did not yet match the catalytic activity of dispersed platinum.…”
Section: Ii2 New Preparation Methods Of Efficient Electrode Catalystsmentioning
confidence: 99%